2018
DOI: 10.1080/13662716.2018.1499502
|View full text |Cite
|
Sign up to set email alerts
|

Innovation strategies, external knowledge and productivity growth

Abstract: This paper studies firms′ capability to recombine internal and local knowledge. It measures the outcome in terms of total productivity growth. Using Swedish data on commuting time for face-to-face contacts across all 290 municipalities, we employ a time-sensitive approach for calculating localized knowledge within a municipality and and its close neighbors. Internal knowledge is captured by register data on firms' innovation intensity. The two sources of knowledge are modeled in a production function setting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The results of this paper are consistent with the current literature on innovation persistence reporting significant individual effects on growth in innovating firms, especially persistent innovators (Cefis and Ciccarelli, 2005;Deschryvere, 2014;Triguero et al, 2014;Lhuillery, 2014;Baum et al, 2015;Ciriaci et al, 2015;Baussola, 2015, 2016;Calvino and Virgillito, 2018;Bianchini and Pellegrino, 2019). Our data show that Australia follows many of the stylized facts on aggregate growth dynamics common to other countries examined to date.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this paper are consistent with the current literature on innovation persistence reporting significant individual effects on growth in innovating firms, especially persistent innovators (Cefis and Ciccarelli, 2005;Deschryvere, 2014;Triguero et al, 2014;Lhuillery, 2014;Baum et al, 2015;Ciriaci et al, 2015;Baussola, 2015, 2016;Calvino and Virgillito, 2018;Bianchini and Pellegrino, 2019). Our data show that Australia follows many of the stylized facts on aggregate growth dynamics common to other countries examined to date.…”
Section: Discussionsupporting
confidence: 90%
“…Research on British, Swedish, Italian, Spanish, Flemish, Finnish and French firms shows strong correlations between innovation persistence and growth in profitability, sales, employment and/or productivity growth (Cefis and Cicarelli, 2005;Czarnitzki and Delanote, 2013;Deschryvere, 2014;Triguero et al, 2014;Lhuillery, 2014;Baum et al, 2015;Baussola, 2015, 2016). It is rare, however, that more than one growth indicator is measured.…”
Section: Introductionmentioning
confidence: 99%
“…A key issue for Cleantech startups is how the entrepreneurial opportunities are combined with the use of firms' internal capabilities. An extensive literature has shown that patents as well as the amount of time and resources invested in R&D are two of the most important proxies for technological capabilities (Baum, Lööf, & Nabavi, 2019;Cefis & Orsenigo, 2001;Peters, 2009).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…A key issue for Cleantech startups is how the entrepreneurial opportunities are combined with the use of firms' internal capabilities. An extensive literature has shown that patents as well as the amount of time and resources invested in R&D are two of the most important proxies for technological capabilities (Baum, Lööf, & Nabavi, ; Cefis & Orsenigo, ; Peters, ). Some studies indicate that such supply‐driven innovations (technological‐push) are particularly important in Cleantech (Horbach, ; Rehfeld, Rennings, & Ziegler, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Total factor productivity (TFP) is a basic concept of the production function and is considered a critical determinant for long-term growth (Mankiw et al, 1992). The literature shows that the main drivers of TFP growth are often categorised into groups: (a) technology and innovation (Baum et al, 2018), (b) financial development and capital investment, including government spending (Zhang & Liu, 2017), (c) labour quality, human capital and knowledge spillovers (Männasoo et al, 2018), (d) institutions and public governance (d’Agostino & Scarlato, 2019) and (e) economic openness and knowledge absorption (Bresnahan et al 2016). However, little attention has been paid to the catalytic role of economic openness through trade liberalisation on productivity growth.…”
Section: Introductionmentioning
confidence: 99%